2007
DOI: 10.1093/icesjms/fsl036
|View full text |Cite
|
Sign up to set email alerts
|

Application and validation of otolith microstructure as a stock identification method in mixed Atlantic herring (Clupea harengus) stocks in the North Sea and western Baltic

Abstract: Clausen, L. A. W., Bekkevold, D., Hatifield, E. M. C., and Mosegard, H. 2007. Application and validation of otolith microstructure as a stock identification method in mixed Atlantic herring (Clupea harengus) stocks in the North Sea and western Baltic. – ICES Journal of Marine Science, 64: 377–385. Herring (Clupea harengus) populations with different spawning times mix in ICES Division IIIa. For stock assessment, otolith microstructure analysis is used to determine the hatching season of individuals, classifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Several otolith-based analyses have shown that individuals hatched in one season may spawn in another (e.g. Aneer 1985, McQuinn 1997b, Brophy et al 2006, but also that spawning-time fidelity is prevalent for East Atlantic herring (Husebø et al 2005, Brophy et al 2006, Clausen et al 2007. Although juvenile growth rate is known to influence age-at-maturity, the general consequences for spawning season are not clear , winter spawners in contrast exhibited a close genetic relationship with the English Channel component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several otolith-based analyses have shown that individuals hatched in one season may spawn in another (e.g. Aneer 1985, McQuinn 1997b, Brophy et al 2006, but also that spawning-time fidelity is prevalent for East Atlantic herring (Husebø et al 2005, Brophy et al 2006, Clausen et al 2007. Although juvenile growth rate is known to influence age-at-maturity, the general consequences for spawning season are not clear , winter spawners in contrast exhibited a close genetic relationship with the English Channel component.…”
Section: Discussionmentioning
confidence: 99%
“…Clupea harengus sampling locations (sample numbers refer to Table 1) (open, black and grey symbols: spring, winter and autumn spawners, respectively) baelt were collected from locations separated by 30 km, the location sampled in winter also acts as a spawning location for spring-spawning components, assumedly representing the same population as the analysed spring spawners. The maturity stage of each fish was recorded using a standard maturation scale (ICES 1962), and the hatching season (the season in which the fish was born) was determined from otoliths using a visual inspection procedure that has been shown to perform reliably across samples and readers (Clausen et al 2007). The latter examinations revealed that the Lillebaelt collections consisted of fish with different hatching times (winter, spring and autumn).…”
Section: Methodsmentioning
confidence: 99%
“…Otolith (sagitta) winter rings were counted as a proxy for age following standard procedures (ICES, 2003). The hatching season of individual fish (spring, autumn or winter) was estimated from otolith central area microstructure according to Clausen et al (2007).…”
Section: Samplingmentioning
confidence: 99%
“…However, there has been little concordance between these characters and genetic differentiation (Ryman et al, 1984; but see Clausen et al, 2007 andJ rgensen et al, 2008). Recent genetic investigations using microsatellite DNA and allozyme markers have found little differentiation among spatially discrete populations in the North Sea, but concordant divergence between the Baltic and North Sea populations Mariani et al, 2005;Larsson et al, 2007Larsson et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The different life-history stages of this herring stock most probably represent key components of the Western Baltic food web. As it is known for other major herring stocks, WBSS is composed of multiple components differentiated by time and area of spawning (Ruzzante et al 2006, Clausen et al 2007 unpublished****). One major component spawns in the vicinity of the German island of Rügen and the associated major spawning ground, the Greifswalder Bodden (GWB), a shallow, semi-enclosed sub-system of estuarine character.…”
Section: Introductionmentioning
confidence: 99%